1994
DOI: 10.1007/bf00192689
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modification of wood by non-formaldehyde cross-linking reagents

Abstract: Using sulfur dioxide (SO 2) as catalyst, wood specimens were treated with nonformaldehyde cross-linking reagents such as glyoxal, glutaraldehyde and dimethylol dihydroxy ethyleneurea (DMDHEU). The results of dimensional stability, acoustic properties, and mechanical strength tests were compared with those obtained from formaldehyde treatment. With glyoxal and glutaraldehyde treatments, antiswelling efficiency (ASE) reached around 70~ which is comparable to the values attained by formaldehyde treatment, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 1 publication
1
9
1
Order By: Relevance
“…Chemical wood modifications, such as acetylation, furfurylation and DMDHEU, increase the dry volume of wood [30,[106][107][108], suggesting the modification chemicals are present within the wood cell wall. An increase in cell wall volume as a result of acetylation has also been demonstrated using helium pycnometry [29,109].…”
Section: Nanopore Blockingmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical wood modifications, such as acetylation, furfurylation and DMDHEU, increase the dry volume of wood [30,[106][107][108], suggesting the modification chemicals are present within the wood cell wall. An increase in cell wall volume as a result of acetylation has also been demonstrated using helium pycnometry [29,109].…”
Section: Nanopore Blockingmentioning
confidence: 99%
“…In DMDHEU-treated wood, cross-links are formed between DMDHEU and the wood polymers thereby making the wood matrix stiffer [108,154]. The change in glass transition temperature of the hemicelluloses might therefore be similar to that in thermally modified wood.…”
Section: Plasticised Hemicellulosesmentioning
confidence: 99%
“…The 2D resin (Dimethylol dihydroxy ethylene urea, DMDHEU) is a typical resin of the nitrogen hydroxymethyl compound with low molecular weight, which has excellent properties in low formaldehyde emission, anti-wrinkle and anti-shrink mechanical properties, and stability, and is used to replace formaldehyde resin in the cotton fiber textile industry and wood modification [29][30][31][32][33]. Some researchers have carried out wood modification studies using 2D resin; the self-polymerization and cross-linking reaction of the 2D resin and wood compounds occurred within the cell wall, resulting in a permanent bulking of the cell wall and leading to a reduction in the swelling and shrinkage properties, thus with the dimensional stability considerably increased.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, good preservative properties and high resistance against white, brown, and soft rot fungi are obtained. The treatments also enhance the wood's acoustic, weathering, and aging properties, furnishing and gluing performances, as well as mechanical properties [30][31][32][33]. However, there are no reports on bamboo culms modification with the 2D resin.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly in this model, the water sorption of woody materials is considered to be composed of the dual sorption processes of the formation of a water monolayer hydrated by hydrogen bonds (hydration process) and the formation of a water polylayer consisting of a solid solution of water in the polymer (dissolution process) through an equilibrium of three chemical species, unhydrated polymer, polymer hydrates and dissolved water. So far, many applications of the H-H model to woody materials have been published (Spalt 1958;Skaar 1972Skaar , 1988Okoh and Skaar 1980;Simpson 1980;Hill et al 2009;Yasuda et al 1994;Yamamoto et al 2005;Zaihan et al 2009). For the constituents of wood, Kelsey (1958, 1959) analyzed the detailed water sorption behavior of cellulose, hemicellulose and lignin and concluded that approximately 80% of water sorption is attributed to hemicellulose and cellulose.…”
Section: Introductionmentioning
confidence: 99%